2022
DOI: 10.1016/j.ejogrb.2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide beliefs among pregnant women on SARS-CoV-2 vaccine: a systematic review

Abstract: Background SARS-CoV-2 vaccine has been recommended to pregnant women, but survey studies showed contrasting findings worldwide in relation to the willingness to accept vaccination during pregnancy. Objective To evaluate the evidence from the literature regarding the acceptance rate of the SARS-CoV-2 vaccine in pregnant and breastfeeding women. Study design: We performed a systematic review on the main databases (MEDLINE (PubMed), Scopus, ISI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 66 publications
1
28
1
3
Order By: Relevance
“…This prevalence is considerably lower than that of pregnant women who expressed the intention to be vaccinated against COVID-19. In particular, two meta-analyses [ 36 , 37 ] found that the global prevalence of pregnant women accepting the COVID-19 vaccine was about 49–54%. Moreover, in a survey with 5282 pregnant women from 16 countries, 52% of them indicated an intention to receive a COVID-19 vaccine [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence is considerably lower than that of pregnant women who expressed the intention to be vaccinated against COVID-19. In particular, two meta-analyses [ 36 , 37 ] found that the global prevalence of pregnant women accepting the COVID-19 vaccine was about 49–54%. Moreover, in a survey with 5282 pregnant women from 16 countries, 52% of them indicated an intention to receive a COVID-19 vaccine [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such recommendations are especially important considering a low acceptance rate for vaccination in pregnancy. A recent systematic review of 15 studies has shown that only 49% of pregnant women are willing to be vaccinated during pregnancy [ 21 ]. However, large trials evaluating the clinical efficacy of the third dose of the vaccine in pregnancy are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence raised the question of the importance of COVID-19 vaccine in pregnant women even in absence of level-1 data on safety of vaccine in this population [65][66][67]. However, since the introduction of vaccinal programs against SARS-CoV-2 infection, pregnant women demonstrated that the anxiety of contracting the infection was not higher than the anxiety of possible adverse events linked to the novel mRNA-based vaccines, with low percentages of acceptance worldwide [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. Indeed, so far reassuring data have been released and published on the importance of vaccine against SARS-CoV-2 during pregnancy, given that antibodies generate a robust humoral immunity in pregnant and lactating women and were also transferred to fetus and neonates through cord blood and breast milk [83][84][85].…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%